The debt brake: business cycle and welfare consequences of Germany's new fiscal policy rule - Eric Mayer; Nikolai Stähler (Deutsche Bundesbank, 2009)
In a New Keynesian DSGE model with non-Ricardian consumers, we show that automatic stabilization according to a countercyclical spending rule following the idea of the debt brake is well suited both to steer the economy and in terms of welfare. In particular, the adjustment account set up to record public deficits and surpluses serves well to keep the level of government debt stable. However, it is essential to design its feedback to government spending correctly, where discretionary lapses should be corrected faster than lapses due to estimation errors.
Keywords: E32; G00; E62; 330; Fiscal policy; debt brake; welfare; dsge; Finanzpolitik; Haushaltsdefizit; Eingebauter Stabilisator; Öffentliche Schulden; Wirtschaftspolitische Wirkungsanalyse; Konjunktur; Wohlfahrtseffekt; Dynamisches Gleichgewicht; Deutschland